Extracellular biosynthesis of water dispersible, protein capped Mn5O8 nanoparticles using the fungus fusarium oxysporum and study of their magnetic behavior - Uddin, Imran; Poddar, Pankaj (Journal of Nanoengineering and Nanomanufacturing, 2013)
Nanomaterials of different sizes, shapes and compositions are being synthesized by various chemical, physical and biological routes. The pressing need of the hour is to have a synthesis protocol which does not harm the environment in any way and is inexpensive so that the benefits can be reaped by all. In this regard, the biological synthesis routes weigh over the chemical and physical ones which are toxic and expensive respectively. The biological routes occur at ambient conditions of temperature, pressure and pH and help protect the ecosystem as these do not employ any hazardous chemicals. Moreover, the nanoparticles obtained via biological routes are naturally protein capped which prevents their agglomeration and helps them retain their shape, size and stability for several months. One such important material is manganese oxide (Mn5O8) which at the nanoscale, has found good use in catalysis and as ionic conductors in fuel cells or batteries. The compound Mn5O8 exists in mixed valences of Mn2+ and Mn4+ and has drawn attention due to its antiferromagnetic nature. Here we report extracellular biosynthesis of manganese oxide (Mn5O8 nanoparticles in the size range of 10–11 nm at room temperature by challenging the fungus Fusarium oxysporum with manganese (II) acetate tetrahydrate [(CH3CO2)2 Mn · 4H2O] as precursor. The Mn5O8 nanoparticles so formed were characterized by TEM, XRD, FTIR, XPS, and TGA. Two mixed manganese ion valencies (Mn2+ and Mn4+) of Mn5O8 have been confirmed by XPS studies and antiferromagnetic transitions by magnetic measurements.